Profilaxis antibiótica en intervenciones odontológicas invasivas en pacientes diabéticos. Hospital Provincial general Docente de Riobamba mayo 2013-mayo 2018 - Dannes Israel Pisango Pila, Pisango Pila (2019)
This research aimed to evaluate the use of antibiotic prophylaxis in invasive dental interventions in diabetic patients treated at the General Hospital of Riobamba from May 2013 to May 2018. It was a bibliographic, observational, descriptive and retrospective study. 170 medical records of diabetic patients treated in the area of dentistry were reviewed, of which 53 patients met the selection criteria by means of an intentional non-probabilistic sampling. The technique used was the observation and its instrument the medical records provided by the hospital, obtaining information from the Automated Daily Registry System of Outpatient Consultations and Attention WEB (RDACAA-WEB) acquiring the numbers of medical records that were subsequently reviewed. The data was analyzed using the statistical software IBM SPSS Statistics v23. The results showed that there was a higher incidence of female patients with 62.3% and 37.7% men, likewise there was a higher incidence in type 2 diabetes mellitus with 90.6%. There was a value of p=0.546 given by the Spearman correlation with respect to the administration of antibiotic in prophylaxis or antibiotic therapy in relation to dental complications. So, it was concluded that there was no relationship between the administration of antibiotic prophylaxis and antibiotic therapy with respect to dental complications